Results of a preliminary palynological analysis at Sibudu Cave - Renaut, R.; Bamford, M. K. (Southern African Humanities, 2021)
Sediment samples excavated from 15 Middle Stone Age lithological horizons within Sibudu Cave (KwaZulu-Natal, South Africa) contain organic material, but only eight samples yielded identifiable pollen grains. The diversity and quantities of palynomorphs are low and this limits potential palaeoenvironmental reconstruction. Identified taxa do, however, support other proxy environmental data for Oxygen Isotope Stage 3. The low quantities and limited diversity of pollen and spores found in the sediments are likely to be the result of destruction from the fires made by people living in the shelter at 60 ka and 50 ka. To cite this paper: Renaut, R. & Bamford, M. K. 2006. Results of a preliminary palynological analysis at Sibudu Cave. Southern African Humanities 18 (1): 235-40.